(untitled) - Kilts, Steve (Hoboken, N.J., 2007)
This book provides the advanced issues of FPGA design as the underlying theme of the work. In practice, an engineer typically needs to be mentored for several years before these principles are appropriately utilized. The topics that will be discussed in this book are essential to designing FPGA's beyond moderate complexity. The goal of the book is to present practical design techniques that are otherwise only available through mentorship and real-world experience.
Keywords: Field programmable gate arrays,Dan dựng cổng chương trình; Design and construction